Simulation in Surgical Education - de Montbrun, Sandra L.; MacRae, Helen (Clinics in Colon and Rectal Surgery, 2012)
The pedagogical approach to surgical training has changed significantly over the past few decades. No longer are surgical skills solely acquired through a traditional apprenticeship model of training. The acquisition of many technical and nontechnical skills is moving from the operating room to the surgical skills laboratory through the use of simulation. Many platforms exist for the learning and assessment of surgical skills. In this article, the authors provide a broad overview of some of the currently available surgical simulation modalities including bench-top models, laparoscopic simulators, simulation for new surgical technologies, and simulation for nontechnical surgical skills.
Keywords: simulation; surgical education; bench models; virtual reality; nontechnical skills